Characterization of [3H] oxymorphone binding sites in mouse brain: Quantitative autoradiography in opioid receptor knockout mice. (16th March 2017) - Yoo, Ji Hoon; Borsodi, Anna; Tóth, Géza; Benyhe, Sándor; Gaspar, Robert; Matifas, Audrey; Kieffer, Brigitte L.; Metaxas, Athanasios; Kitchen, Ian; Bailey, Alexis
Highlights: The anatomical distribution of oxymorphone is similar to the mu opioid (MOP) receptor agonist [ 3 H]DAMGO. MOP receptor is the main binding target for oxymorphone in mouse brain tissue. The pharmacological effect of oxymorphone is most likely to be mediated via a MOP dependent mechanism. Abstract: Oxymorphone, one of oxycodone's metabolic products, is a potent opioid receptor agonist which is thought to contribute to the analgesic effect of its parent compound and may have high potential abuse liability. Nonetheless, the in vivo pharmacological binding profile of this drug is still unclear. This study uses mice lacking mu (MOP), kappa (KOP) or delta (DOP) opioid receptors as well as mice lacking all three opioid receptors to provide full characterisation of oxymorphone binding sites in the brain. Saturation binding studies using [ 3 H]oxymorphone revealed high affinity binding sites in mouse brain displaying K d of 1.7 nM and B max of 147 fmol/mg. Furthermore, we performed quantitative autoradiography binding studies using [ 3 H]oxymorphone in mouse brain. The distribution of [ 3 H]oxymorphone binding sites was found to be similar to the selective MOP agonist [ 3 H]DAMGO in the mouse brain. [ 3 H]Oxymorphone binding was completely abolished across the majority of the brain regions in mice lacking MOP as well as in mice lacking all three opioid receptors. DOP and KOP knockout mice retained [ 3 H]oxymorphone binding sites suggesting oxymorphone may not target DOP or KOP. These results confirm that the MOP, and not the DOP or the KOP is the main high affinity binding target for oxymorphone.